2012
DOI: 10.1016/j.wneu.2011.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Operation-Microscope-Mounted Touch Display Tablet Computer for Intraoperative Imaging Visualization

Abstract: OBJECTIVE:The authors have developed a novel sterile draped touch display solution for convenient intraoperative access to imaging data. This study describes the technology and clinical experience with the system. METHODS: We developed a flexible-mounted touch display tablet PC (Apple iPad) that allows fixation of the display on the operation microscope and fine adjustments during the surgery when the microscope is moved. We compared this setup with a conventional wall-mounted flat-panel and a mobile display s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…One such study demonstrated that the high resolution display of the iPad performed equally to conventional desktop LCD monitors in preliminary interpretation of emergent CT brain exams after minor modifications were made to the iPad’s zoom function capabilities [23]. Sterile tablet computers have been successfully utilized in the operating room by neurosurgeons as a substitution to expensive commercial intraoperative imaging equipment for image guidance during tumor resection procedures [24]. Another recent publication found Internal Medicine residents felt subjectively more efficient on the wards when they were provided with iPad tablets loaded with the hospital electronic medical record access program.…”
Section: Introductionmentioning
confidence: 99%
“…One such study demonstrated that the high resolution display of the iPad performed equally to conventional desktop LCD monitors in preliminary interpretation of emergent CT brain exams after minor modifications were made to the iPad’s zoom function capabilities [23]. Sterile tablet computers have been successfully utilized in the operating room by neurosurgeons as a substitution to expensive commercial intraoperative imaging equipment for image guidance during tumor resection procedures [24]. Another recent publication found Internal Medicine residents felt subjectively more efficient on the wards when they were provided with iPad tablets loaded with the hospital electronic medical record access program.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to perform a head-tohead comparison of these devices, though prior studies analyzing the iPad and Kinect individually have reported a generally positive response towards their utility in the operative environment [11,13,14,[16][17][18][19]. Most users favored the usability of the iPad (mean score of 13.5) in almost every basic interaction over the Loop Pointer (12.9) and Kinect (9.9; Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Both measures corresponded; namely, the Kinect has least concern and the iPad has the most concern in jeopardizing the sterile field. Notably, prior studies have employed varying techniques to allow for sterility, including sealing the unit between two pieces of Tegaderm by a sterile operator [13], use of a sterile-wrapped iPad touch-display system mounted on an operation microscope positioned just above the surgeon for neurosurgical application [14], and sterile-bagged iPad intra-operative CT image review during lung segmentectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such systems are mainly based on voice control devices and touch-sensitive panels. [5][6][7][8] However, their use may be associated with problems related to misrecognition of commands or the necessity of sterile isolation. On the other hand, the majority of currently available motion recognition devices are typically driven by attached color, electronic, or infrared markers or sensors fixed on the body of the operator.…”
Section: Discussionmentioning
confidence: 99%